Integrasi Kearifan Lokal dalam Pendidikan Sains debagai Strategi Pengembangan Kompetensi Masa Depan Peserta Didik - Fonny Katili; I Wayan Suastra; I Made Citra Wibawa; Ida Bagus Putu Arnyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the role of integrating local wisdom into science education as a strategy for developing students’ future competencies. The method used is a systematic literature study of scientific articles, books, and educational policy documents published between 2010 and 2024 that are relevant to science education, local wisdom, and 21st-century competencies. The results indicate that integrating local wisdom into science education strengthens scientific literacy, fosters ecological character, and enhances students’ critical and reflective thinking skills. In conclusion, the integration of local wisdom in science learning can serve as a contextual and transformative learning strategy that supports the development of adaptive, creative, and culturally grounded 21st-century learners oriented toward sustainable development. Keywords: Future Competencies, Local Wisdom, Science Education, Scientific Literacy, Sustainable Education